PERATURAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2015 TENTANG TATA CARA PENYELESAIAN GUGATAN SEDERHANA SEBAGAI INSTRUMEN PERWUJUDAN ASAS PERADILAN SEDERHANA, CEPAT DAN BIAYA RINGAN - Riskawati, Shanti (Veritas et Justitia, 2018)
There is a need to conduct business transactions rapidly and in a quick perfunctory manner.  At the same time arose also the need to develop and implement a quick, simple and cost efficient business dispute settlement procedure.  In response to this need, the Indonesian Supreme Court issued regulation no. 2 of 2015 re. procedure for filing simple civil claims. The legal issue to be discussed here, using a juridical normative or dogmatic approach, is whether this regulation succeed in fulfilling its promise to provide for a quick, simple and cost efficient civil claim examination procedure? The answer to this question is sought, in addition to the method mentioned above, by comparing the procedure provided by the Supreme Court regulation with the existing model of civil claim court examination procedure.  By virtue of this comparison the strength and weakness of the Supreme Court dispute settlement model can be analyzed.